Controle dinâmico de potência em redes Wi-SUN/IEEE 802.15.4g em topologia linear - Saraiva, Frederico Augusto Monteiro (2020)
Nowadays, the development of information tecnologies mean that we live in a connected world, where pervasive computing is increasingly present in society. Therefore, wireless sensor networks (WSNs) are vital components in the construction of this connection infrastructure. Wi-SUN networks are a kind of RSSF that, by its nature, has mesh topology as the most adopted. In this way, they also carry with them the need for transceivers’redundancy. Some uses of Wi-SUN networks require that the transceivers should be interconnected in a linear form. At such times, the failure of one of the transceivers may lead to extensive damage due to the disruption of the information path, since the linear form of interconnection does not offer alternative routes for the traffic. Thereby, this research has its main hypothesis the need that every Wi-SUN network should be as resilient as possible. As secondary hypothesis, it’s expected that a possible redundancy for a linearly arranged system is that the failure of a node may be mitigated if its neighboring nodes increase their transmission power, in order to supplant the defective node and, with this, be able to pass on the information. This research aims to analyze how a Wi-SUN/802.15.4g network may remain as operational as possible when the transceivers are arranged linearly and there is a failure in one of the nodes, based on experimental data obtained in an Smart Campus environment and the development and presentation of strategies for dynamic power control.